The Role of English Learning Motivation in Enhancing Students’ Reading Comprehension - Susiani; Fitri Rizki (Jurnal Manajemen, Pendidikan Dan Ilmu Komputer, 2026)
This study investigates the role of English learning motivation in enhancing students’ reading comprehension in an English as a Foreign Language (EFL) context. Motivation is widely acknowledged as a key factor influencing language learning success, particularly in reading comprehension, which requires cognitive engagement and sustained effort. This research employed a quantitative correlational design involving 60 eleventh-grade students. Data were collected using a motivation questionnaire and a reading comprehension test. The results revealed a significant positive correlation between students’ motivation and their reading comprehension ability (r = 0.65, p < 0.05). The findings indicate that highly motivated students tend to demonstrate better comprehension skills. The study suggests that fostering both intrinsic and extrinsic motivation can significantly improve students’ reading outcomes. Therefore, educators are encouraged to apply motivational strategies in teaching reading.